Endophytic Fungi-Alternative Sources of Cytotoxic Compounds: A Review - Fazilath Uzma; Chakrabhavi D. Mohan; Abeer Hashem; Narasimha M. Konappa; Shobith Rangappa; Praveen V. Kamath; Bhim P. Singh; Venkataramana Mudili; Vijai K. Gupta; Chandra N. Siddaiah; Srinivas Chowdappa; Abdulaziz A. Alqarawi; et al. (Frontiers Media S.A., 2018)
Cancer is a major cause of death worldwide, with an increasing number of cases being reported annually. The elevated rate of mortality necessitates a global challenge to explore newer sources of anticancer drugs. Recent advancements in cancer treatment involve the discovery and development of new and improved chemotherapeutics derived from natural or synthetic sources. Natural sources offer the potential of finding new structural classes with unique bioactivities for cancer therapy. Endophytic fungi represent a rich source of bioactive metabolites that can be manipulated to produce desirable novel analogs for chemotherapy. This review offers a current and integrative account of clinically used anticancer drugs such as taxol, podophyllotoxin, camptothecin, and vinca alkaloids in terms of their mechanism of action, isolation from endophytic fungi and their characterization, yield obtained, and fungal strain improvement strategies. It also covers recent literature on endophytic fungal metabolites from terrestrial, mangrove, and marine sources as potential anticancer agents and emphasizes the findings for cytotoxic bioactive compounds tested against specific cancer cell lines.